2019
DOI: 10.13057/biodiv/d200601
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of current threats to the existence of Brackenridgea zanguebarica in a small geographic area in Vhembe, Limpopo Province, South Africa

Abstract: Abstract. Tiawoun MAP, Tshisikhawe MP, Gwata ET. 2019. Geometric morphometry of pupae to identify four medically important flies (Order: Diptera) in Thailand. Biodiversitas 20: 1504-1509. Brackenridgea zanguebarica is one of the most threatened plant species in South Africa, found only in Thengwe village, Vhembe District Municipality, Limpopo Province, South Africa. Due to the high traditional use of its stem bark and root, the species is now facing the threat of extinction. It has been assessed in accordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The implication of muthi traders being primarily to blame for breaking the rules was not an unexpected result. It is a widely held perception that many medicinal traders are more concerned with income generation than species' sustainability (Moeng and Potgieter 2011;Tiawoun et al 2019). The mention of a fine for lawbreakers is similar to Igboin (2016) findings in Nigeria, where lawbreakers are required to bring a token of palm wine or oil to TLs.…”
Section: The Use Of Traditional Rules As a Management Toolmentioning
confidence: 75%
See 1 more Smart Citation
“…The implication of muthi traders being primarily to blame for breaking the rules was not an unexpected result. It is a widely held perception that many medicinal traders are more concerned with income generation than species' sustainability (Moeng and Potgieter 2011;Tiawoun et al 2019). The mention of a fine for lawbreakers is similar to Igboin (2016) findings in Nigeria, where lawbreakers are required to bring a token of palm wine or oil to TLs.…”
Section: The Use Of Traditional Rules As a Management Toolmentioning
confidence: 75%
“…Some of these traditional rules are common to other parts of South Africa (Petersen et al 2017) and other African countries, such as Kenya (Monica et al 2016) and Tanzania (Kangalawe et al 2014), though different rules have been reported by other studies, especially in South Africa. In the Vhembe District, for example, collection of species, including Brackenridgea zanguebarica is allowed under the supervision of an officer from the tribal authority to ensure sustainability (Tiawoun et al 2019). Collection of plants in general, including Alepidea amatymbica in the Eastern Cape, is done via a permit from tribal offices (Stoffersen et al 2011).…”
Section: The Use Of Traditional Rules As a Management Toolmentioning
confidence: 99%
“…This study argued that the smaller the population size of individuals of threatened plants in a single area of occupancy, the more vulnerable towards the verge of extinction they become. Brackenridgea zanguebarica is considered Critical Endangered in South Africa and its distribution range is restricted to a single geographic area or area of occupancy called Thengwe (Tiawoun et al 2019).…”
Section: Distribution and Populationmentioning
confidence: 99%